Guiding responsible AI in healthcare in the Philippines - Raymond Francis R. Sarmiento; Shauna M. Overgaard; Chenyu Gai; Joshua D. Overgaard; Joshua W. Ohde (npj Digital Medicine)
Abstract The Philippines faces significant barriers to the safe and effective deployment of AI in healthcare. By leveraging lessons learned from other Southeast Asian nations, the European Union, and the United States, the Philippines can develop a national strategy to deploy AI in healthcare. Drawing from experiences of other nations, we provide considerations, foundational recommendations, and relevant resources to assist leaders in developing and adopting responsible AI in Philippine healthcare.